The Construction Of Religious Moderation In Education At Ma'had Al-Jamiah: A Study Of Inhibiting And Supporting Factors - Mujab, Saiful; Budhi, Henry Setya; Failasufa, Anisatul; Koto, Rahmayati (Jurnal Penelitian, 2025)
This study aims to analyze the construction of religious moderation education at Ma'had Al-Jami'ah UIN Walisongo by examining the supporting and inhibiting factors of its implementation. Using the qualitative case study method, data was collected thru in-depth interviews, participant observation, and document review, and analyzed interactively thru reduction, presentation, and conclusion drawing. The research findings indicate that the program's success is supported by institutional commitment, an integrated curriculum, and the unique culture of the Ma'had, which emphasizes living values, the role of the mudabbir/mudabbirah, and the social dynamics of the dormitory. However, limited resources, external environmental influences, the diversity of santri backgrounds, and unsynchronized regulations are the main constraints. Theoretically, this research offers a new understanding of ecosystem-based religious moderation in PTKIN dormitories, an aspect that has not been widely discussed in the literature. Practically, this finding confirms Ma'had Al-Jami'ah UIN Walisongo as a strategic space for the formation of moderate character that is contextual, inclusive, and sustainable.